The Rights of People with Special Needs in Media Laws in the Kurdistan Region - ئه‌حمه‌د, پ.ی.د. كارزان محه‌مه‌د (Sulaimani Journal for Humanities, 2025)
The rights of special needs people, as an important section of society, have been guaranteed by special agreements at the international level, and most countries treat them according to humanitarian principles. This study, which focuses on the position of the rights of people with special needs, attempts to answer a question based on the interpretation of journalism laws: To what extent the rights of people with special needs are respected and protected against dangers and violations? Are they reflected in journalistic laws? What are the legal procedures for directing media institutions to serve people with special needs? What are the shortcomings of the journalism laws in the Kurdistan Region in this regard and to what extent have they created obstacles to the application of the rights of people with special needs? The main purpose of this study is to discuss all the legal aspects of the rights of people with disabilities and to present the position and respect of this right in the applicable laws of journalism, in the Kurdistan Region, according to official statistics, there are a large number of people with special needs. To answer the questions of the research and achieve its objectives, the researcher based on the analytical method and grounded theory, tries to evaluate the content of all the laws related to the media in the Kurdistan Region, positive aspects and to present their negative points, so that the rights of this group can be treated more correctly and humanely in the future. At the end of the study, the results of the assessment of the treatment of journalism laws and their level of attention to the rights of this group are presented, then includes several recommendations to guide the parliament and the KRG in Drafting new laws and guidelines for the rights of people with special needs, in line with the international human rights standards. It is also a clarity for the group to become familiar with their rights.
Keywords: Rights of individuals with special needs; journalism laws; Kurdistan region